Performance of Dual Purpose Barley Genotypes for Green Fodder by AMMI Analysis - Verma, Ajay; Verma, R. P. S.; Kharab, A. S.; Kumar, Vishnu; Gupta, R. K. (International Journal of Bio-resource and Stress Management, 2016)
Highly significant effects were observed for green fodder yield of dual purpose barley for environments, genotypes and interactions. Environmental effects accounted for the major portion of the total variance as of 82.3%. Significant interaction effects were partitioned further into IPCA1, IPCA2, IPCA3, IPCA4; which explained 30.4, 19.4, 14.8, 13.2% respectively. MASV indicated that genotypes UPB 1035, BH 970, RD 2035, UPB 1034, RD 2857 and KB 1238 were stable; whereas, genotypes RD 2857 and RD 2035 were the stable genotypes with relatively more average yield. SIPC4 identified AZAD, RD 2856, UPB 1034, BH 970 and RD 2858 as stable genotypes. AMMI distance ranked genotypes in order of preference as RD 2035<BH 970<RD 2857<UPB 1035<UPB 1034. Least ASV score associated with UPB 1035, followed by UPB 1034, UPB 1036 and BH 971. Positive and negative IPCA1values had been observed for large number of genotypes. Genotype AZAD had large negative IPCA1 score along with positive IPCA4 as this reflected crossover type G×E interaction. RD 2715, RD 2857 and RD 2859 genotypes expressed yields greater than the overall mean and positive IPCA1 scores. Lower MASV observed for Vijapur, Banswara and Bikaner conditions where SIPC4 pointed towards Hisar, Bikaner and Varanasi as favorable locations. AMMI distance values identified Vijapur, Udaipur and Varanasi locations.